2012
DOI: 10.5301/ru.2012.9364
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Antibiotic and Anti-Inflammatory Therapy on Serum Prostate Specific Antigen in Asymptomatic Men: Our Experience

Abstract: A combination of antibiotic and anti-inflammatory therapy seems to be a useful way to avoid unnecessary biopsies in patients with PSA range from 4 to 10 ng/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…After use of antibiotic therapy, the PSA level was normalised by a wide variety of percentages, ranging from 16% to 59% [6-8,10,20,25,29,30]. Furthermore, the range of the PSA level decrease was 17-80% [4,13,15,18,20,23,29,32], or a > 20% decrease from baseline [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After use of antibiotic therapy, the PSA level was normalised by a wide variety of percentages, ranging from 16% to 59% [6-8,10,20,25,29,30]. Furthermore, the range of the PSA level decrease was 17-80% [4,13,15,18,20,23,29,32], or a > 20% decrease from baseline [24].…”
Section: Discussionmentioning
confidence: 99%
“…Six studies used ofloxacin [4,8,10,13,15,16], six studies used 500 mg ciprofloxacin [5,9,17,19,21,23], and five used levofloxacin [6,9,12,28]. Six studies combined the antibiotic therapy with NSAIDs [4,5,18,20,23,25]. Huang et al [21] added the plant extracts, Ningbitai and Yunnan Baiyao capsule, to the antibiotic therapy.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach, however, requires careful follow-up, especially for patients whose PSA levels fail to decrease to within the normal range ( 26 , 27 ). Kaygisiz ( 1 ) and Del Rosso ( 19 ) suggested that AT should be administered for 3 weeks, regardless of the presence of inflammation when PSA levels are in the grey zone, before making a decision regarding whether or not to carry out a biopsy.…”
Section: Discussionmentioning
confidence: 99%